The Brandt Line after forty years: The more North–South relations change, the more they stay the same?. Issue 1 (16th January 2021) - Lees, Nicholas
Abstract: The Brandt Line is a way of visualising the world that highlights the disparities and inequalities between the wealthy North and the poorer Global South. Forty years after its popularisation as part of a call for global reform, is the Brandt Line now a misleading way of representing world politics? This article assesses whether the Global South has lost its distinctiveness and coherence relative to the North since 1980. Existing assessments of global inequality do not settle the question of whether the North–South divide remains relevant for international relations because they overlook the most politically significant measures of inequality. Drawing on power transition theory, this article provides a systematic assessment of the North–South divide in terms of levels of economic development, relative inequality, economic power, and political satisfaction. The evidence suggests that the Brandt Line is largely intact. Although the economic diversity of the South has increased and its collective economic power has risen, relative income rankings remain unaltered and the states of the Global South are as dissatisfied as they were four decades ago. Differential growth rates are reshaping world politics without eroding the North–South divide traced by the Brandt Line.